Inside Back Cover: Polymer Nanofiber‐Embedded Microchips for Detection, Isolation, and Molecular Analysis of Single Circulating Melanoma Cells (Angew. Chem. Int. Ed. 12/2013). Issue 12 (26th February 2013) - Hou, Shuang; Zhao, Libo; Shen, Qinglin; Yu, Juehua; Ng, Charles; Kong, Xiangju; Wu, Dongxia; Song, Min; Shi, Xiaohong; Xu, Xiaochun; OuYang, Wei‐Han; He, Rongxian; et al.
<x xml:space="preserve">Abstract</x> Transparent polymer‐nanofiber substrates combined with a laser microdissection technique, produced a new single‐cell isolation technology, as shown by M. A. Garcia, A. Ribas, R. S. Lo, H.‐R. Tseng, et al. in their Communication on page 3379 ff. Using this new technique, single circulating melanoma cells (CMCs) were isolated from patients' blood for subsequent single‐cell genotyping to identify a mutation in a proto‐oncogene BRAF.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>